Media Analysis of Racism and Speciesism (MARS) test finds Oscars so AnthropoScenic in contemporary animated films - Khazaal, Natalie; Gorsevski, Ellen; Linné, Tobias (Frontiers in Communication, 2026)
IntroductionAnimation transfers human races into animals, serving as a prime site for speciesism and racism.MethodsTesting this observation on recent examples, our quantitative/qualitative study delves into a nine-year (2016-2024) span of Oscar-nominated animated feature and short films. We theorize how to make incisive, quantitative/qualitative, balanced trans-species intersectionality the foundation of critical research on racism and speciesism. We offer the Media Analysis of Racism and Speciesism Test (MARS test), a practical tool accessible to scholars, creators, and general viewers for analyzing character portrayals and interactions, helping identify and challenge normalized racist and speciesist storylines.ResultsInsufficient number of films yielded transspecies allyship.DiscussionThe MARS test is for anyone who is interested in ways film and other media offer questionable implications regarding racism and speciesism that call for accountability.